Enhancing Early Literacy Through Collaborative Digital Educational Games: A Classroom Action Research with Kindergarten Children Exhibiting ADHD Symptoms - Asmawati, Septi; Mahabbati, Aini (Papanda Publisher, 2025)
Early literacy development presents significant challenges for kindergarten children exhibiting Attention Deficit Hyperactivity Disorder (ADHD) symptoms, who often struggle with concentration and traditional instructional methods. This study investigated the effectiveness of collaborative digital educational games in enhancing early literacy capabilities among children with ADHD symptoms. A classroom action research design following the Kemmis and McTaggart model was implemented over six months with a 5-6 year old male kindergarten student exhibiting ADHD symptoms. The intervention utilized the